Effect of geometrical parameters on turbulent flow and heat transfer behaviors in triple-start corrugated tubes - Pitak PROMTHAISONG; Withada JEDSADARATANACHAI; Smith EIAMSA-ARD (My University, 2018)
Computational results of flow structure, pressure loss and heat transfer characteristics in triple-start corrugated tubes are reported. The influences of the depth ratio (DR = 0.02, 0.04, 0.06, 0.08, 0.1, 0.12, 0.14 and 0.16) and pitch ratio (PR = 0.5, 0.65, 0.75, 1.0, 1.5 and 2.0) were investigated in turbulent flow regime, Re = 5000 to 20,000. The computational results indicated that the triple-start corrugated tubes generate main swirl flow and helical swirl flow which helps to reduce the thermal boundary layer thickness and enhance the heat transfer rate. The flow and heat transfer become under fully developed periodic condition around x/D = 6.0. The friction factor monotonically increases with the rise of DR values and decrease PR values while maximum heat transfer rate is found at DR = 0.08 and PR = 0.75. Nusselt numbers and friction factors of triple-start corrugated tubes in the investigated range are found to be 0.8 to 2.31 and 1.0 to 17.14 times over those of the straight circular smooth tube, respectively. For the range studied, the triple-start corrugated tube with DR = 0.06 and PR = 0.75 offers the maximum thermal enhancement factor of 1.21 at Re = 5000.
Keywords: Heat transfer enhancement; Friction Factor; Fluid Dynamics and Turbulent Flows